Strong correlation between the rates of intrinsically antibiotic-resistant species and the rates of acquired resistance in Gram-negative species causing bacteraemia, EU/EEA, 2016 - Jarlier, Vincent; Diaz Högberg, Liselotte; Heuer, Ole E; Campos, José; Eckmanns, Tim; Giske, Christian G; Grundmann, Hajo; Johnson, Alan P; Kahlmeter, Gunnar; Monen, Jos; Pantosti, Annalisa; Rossolini, Gian Maria; et al. (Euro surveillance, 2019)
BackgroundAntibiotic resistance, either intrinsic or acquired, is a major obstacle for treating bacterial infections.AimOur objective was to compare the country-specific species distribution of the four Gram-negative species Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter species and the proportions of selected acquired resistance traits within these species.MethodWe used data reported for 2016 to the European Antimicrobial Resistance Surveillance Network (EARS-Net) by 30 countries in the European Union and European Economic Area.ResultsThe country-specific species distribution varied considerably. While E. coli accounted for 31.9% to 81.0% (median: 69.0%) of all reported isolates, the two most common intrinsically resistant species P. aeruginosa and Acinetobacter spp. combined (PSEACI) accounted for 5.5% to 39.2% of isolates (median: 10.1%). Similarly, large national differences were noted for the percentages of acquired non-susceptibility to third-generation cephalosporins, carbapenems and fluoroquinolones. There was a strong positive rank correlation between the country-specific percentages of PSEACI and the percentages of non-susceptibility to the above antibiotics in all four species (rho > 0.75 for 10 of the 11 pairs of variables tested).ConclusionCountries with the highest proportion of P. aeruginosa and Acinetobacter spp. were also those where the rates of acquired non-susceptibility in all four studied species were highest. The differences are probably related to national differences in antibiotic consumption and infection prevention and control routines.
Keywords: antimicrobial resistance; Gram-Negative Bacterial Infections; Europe; bloodstream infection; mikrobiální testy citlivosti; Escherichia coli; Sentinel Surveillance; Carbapenems; bacterial infections; lidé; Gram-Negative Bacteria; Evropa; gramnegativní bakteriální infekce; Evropská unie; Anti-Bacterial Agents; Fluoroquinolones; Bacteremia; fluorochinolony; bakteriální léková rezistence; cefalosporiny; bakteriemie; sentinelová surveillance; Microbial Sensitivity Tests; gramnegativní bakterie; Cephalosporins; Acinetobacter; Pseudomonas aeruginosa; European Union; karbapenemy; antibakteriální látky; Drug Resistance, Bacterial; Klebsiella pneumoniae; Gram-negative bacilli; antibiotic resistance; Humans